RECONSTRUCTION OF THE TECTONIC STRESS FIELD IN THE DEEP PARTS OF THE SOUTHERN KURIL-KAMCHATKA AND NORTHERN JAPAN SUBDUCTION ZONES - D. A. Safonov (Геодинамика и тектонофизика, 2020)
Earthquake focal mechanisms in the Southern Kuril-Kamchatka and Northern Japan subduction zones were analysed to investigate the features of the tectonic stress field inside the Pacific lithospheric plate subducting into the upper mantle. Earthquake focal mechanism (hypocenter depths of more than 200 km) were taken from the 1966– 2018 NIED, IMGiG FEB RAS and GlobalCMT catalogues. The tectonic stress field was reconstructed by the cataclastic analysis method, using a coordinate system related to the subducting plate. In most parts of the studied seismic focal zone, the axis of the principal compression stress approximately coincides with the direction of the Pacific lithospheric plate subduction beneath the Sea of Okhotsk. It slightly deviates towards the hinge zone separating the studied regions. The principal tension stress axis is most often perpendicular to the plate movement, but less stable in direction. This leads to compression relative to the slab in some parts of the studied regions, and causes shearing in others. The hinge zone is marked by the unstable position of the tension axis and high values of the Lode–Nadai coefficient, corresponding to the conditions of uniaxial compression, while the compression direction remains the same, towards the slab movement. Two more areas of uniaxial compression are located below the Sea of Japan at depths of 400–500 km.